5-hydroxymethylfurfural content in selected gluten- and gluten-free cereal food products - Mańkowska, Dorota; Majak, Iwona; Bartos, Adrian; Słowianek, Marta; Łącka, Agata; Leszczyńska, Joanna (Lodz University of Technology Press, 2017)
5-Hydroxymethylfurfural (HMF) was determined with HPLC method in forty one food samples, including gluten-free, breakfast cereals and bakery products. The highest concentration of HMF was found in wheat bread with cranberries (210 mg kg-1) and in breakfast cereals – honey wheat loops (85.099 mg kg-1). In contrast, wholegrain oatmeal and gluten-free sponge cakes had the lowest HMF level of all tested samples, below the detection limit and 0.485 mg kg-1, respectively. In most cases, lack of gluten coincided with the lowest HMF content readings (average 8.488 mg kg-1). The impact of the type of sugar, especially glucose, on the HMF concentration in food is apparent. Sweetened breakfast cereals, with the average content of HMF at 25.55 mg kg-1, took lead over dietary products (8.488 mg kg-1) and bakery products (18.395 mg kg-1), with the exception for wheat bread with cranberries. These cereals contained glucose or glucose-fructose syrup.
Keywords: hydroxymethylfurfuralL; gluten; gluten-free products; breakfast cereals; bakery products; produkty bezglutenowe; płatki zbożowe; pieczywo